A dual fuel ICE diesel-H2 featuring 1, 600 bar cryogenic liquid H2 injection. (25th May 2021) - Boretti, Alberto
Abstract: Dual fuel internal combustion engines (ICEs) using diesel and fuels that are vaporous in normal conditions are collecting consideration for two motives. First is the occasion to achieve diesel-like power density ϕ and fuel conversion efficiency η steady-state, and similar transient performances. Second, is the chance to deliver better than diesel engine-out emissions, for CO2, particulate matter, unburned hydrocarbons, and nitrous oxides. A high-pressure (HP) cryogenic liquid injector is proposed for H2 and applied to a high compression ratio high boost ICE featuring 2 direct injections (DI) injectors per cylinder, 1 diesel, and 1H2 . Super-turbocharging (mechanically assisted turbocharging) is employed to make better steady-state performances, especially low-speed high-load, but also high-speed high-load, and transients, principally eliminating the turbo-lag. This work aims at evaluating the benefits of further increasing the injection pressure of the cryogenic hydrogen in a specific dual fuel diesel-hydrogen engine setting. With the proposed 1600 bar injector, this ICE delivers top η>52%, and higher η>40% over most of the speed-load range, with the option to further increase ϕ vs. the baseline diesel working less lean at top loads and adopting mixed premixed-diffusion combustion modes. Highlights: Injection shaping in compression ignition engines is a driver of improved fuel conversion efficiency. A dual-fuel engine is considered, with two separate injectors, one for the diesel, and one for hydrogen. The proposed 1600 bar hydrogen injector permits almost the same as diesel injection shaping. Numerical engine experiments deliver fuel conversion efficiencies up to 52%.